2021
DOI: 10.1007/s13679-021-00459-5
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Outcomes in Minority Ethnic Groups: Do Obesity and Metabolic Risk Play a Role?

Abstract: Purpose of Review Globally, minority ethnic groups have been at higher risk of COVID-19 mortality and morbidity than majority populations. This review outlines factors that may interact to create these inequalities and explores the hypothesis that differing levels of cardio-metabolic risk, according to ethnic group, play a role. Recent Findings Two UK Biobank studies have reported that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Obese communities have less access to healthy food while non-obese communities have greater access to healthy food. The findings contribute to the epidemiological inequality and urban development research regarding roles of obesity and food environment in inequalities related to COVID-19 outcomes [79]. COVID-19 has exposed existing obesity inequalities in a new context for Chicago, making healthy food access challenging and, thus, leading to further diffusion of the virus.…”
Section: Discussionmentioning
confidence: 80%
“…Obese communities have less access to healthy food while non-obese communities have greater access to healthy food. The findings contribute to the epidemiological inequality and urban development research regarding roles of obesity and food environment in inequalities related to COVID-19 outcomes [79]. COVID-19 has exposed existing obesity inequalities in a new context for Chicago, making healthy food access challenging and, thus, leading to further diffusion of the virus.…”
Section: Discussionmentioning
confidence: 80%
“…Even after considering for ethnicity, it was shown that obesity was associated with adverse outcome as suggested by an increase in hospital admission, ICU/IMV requirement, and mortality. Although this was seen across Chinese, South Asian, and Arab ethnicities, this association was most prominent in populations with Black ethnicity [ 99 101 ].…”
Section: Obesity a Potential Risk For Covid-19-epidemiological Evidencementioning
confidence: 99%